Leachates from plants recently infected by root-feeding nematodes cause increased biomass allocation to roots in neighbouring plants - Zhang, Peihua; Bonte, Dries; De Deyn, Gerlinde B.; Vandegehuchte, Martijn L. (Scientific reports, 2021)
Plants can adjust defence strategies in response to signals from neighbouring plants attacked by aboveground herbivores. Whether similar responses exist to belowground herbivory remains less studied, particularly regarding the spatiotemporal dynamics of such belowground signalling. We grew the grass Agrostis stolonifera with or without root-feeding nematodes ( Meloidogyne minor ). Leachates were extracted at different distances from these plants and at different times after inoculation. The leachates were applied to receiver A. stolonifera plants, of which root, shoot, and total biomass, root/shoot ratio, shoot height, shoot branch number, maximum rooting depth and root number were measured 3 weeks after leachate application. Receiver plants allocated significantly more biomass to roots when treated with leachates from nematode-inoculated plants at early infection stages. However, receiver plants’ root/shoot ratio was similar when receiving leachates collected at later stages from nematode-infected or control plants. Overall, early-collected leachates reduced growth of receiver plants significantly. Plants recently infected by root-feeding nematodes can thus induce increased root proliferation of neighbouring plants through root-derived compounds. Possible explanations for this response include a better tolerance of anticipated root damage by nematodes or the ability to grow roots away from the nematode-infected soil. Further investigations are still needed to identify the exact mechanisms.